Body Size, Rather Than Male Eye Allometry, Explains Chrysomya megacephala (Diptera: Calliphoridae) Activity in Low Light. Issue 1 (25th September 2015) - Smith, J. L.; Palermo, N. A.; Theobald, J. C.; Wells, J. D.
Abstract : Male Chrysomya megacephala (F.) blow fly compound eyes contain an unusual area of enlarged dorsal facets believed to allow for increased light capture. This region is absent in females and has been hypothesized to aid in mate tracking in low light conditions or at greater distances. Many traits used in the attraction and capture of mates are allometric, growing at different rates relative to body size. Previous reports concerning C. megacephala eye properties did not include measurements of body size, making the relationship between the specialized eye region and body size unclear. We examined different morphological features of the eye among individuals of varying sizes. We found total eye size scaled proportionately to body size, but the number of enlarged dorsal facets increased as body size increased. This demonstrated that larger males have an eye that is morphologically different than smaller males. On the basis of external morphology, we hypothesized that since larger males have larger and a greater number of dorsally enlarged facets, and these facets are believed to allow for increased light capture, larger males would be active in lower light levels than smaller males and females of equal size. In a laboratory setting, larger males were observed to become active earlier in the morning than smaller males, although they did not remain active later in the evening. However, females followed the same pattern at similar light levels suggesting that overall body size rather than specialized male eye morphology is responsible for increased activity under low light conditions.